2017
DOI: 10.1098/rsob.170061
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box transcription factor L2 activates Fcp3C to regulate insect chorion formation

Abstract: Most animals are oviparous. However, the genes regulating egg shell formation remain not very clear. In this study, we found that Nilaparvata lugens Forkhead box transcription factor L2 (NlFoxL2) directly activated follicle cell protein 3C (NlFcp3C) to regulate chorion formation. NlFoxL2 and NlFcp3C had a similar expression pattern, both highly expressed in the follicular cells of female adults. Knockdown of NlFoxL2 or NlFcp3C also resulted in the same phenotypes: obesity and female infertility. RNA interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…D). Follicle cell protein 3C (Fcp3C) was identified to be involved in eggshell formation in insects such as Drosophila melanogaster (Burke et al , ) and N. lugens (Ye et al , ). In female adult BPHs, the expression pattern of NlChP38 was consistent with Fcp3C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D). Follicle cell protein 3C (Fcp3C) was identified to be involved in eggshell formation in insects such as Drosophila melanogaster (Burke et al , ) and N. lugens (Ye et al , ). In female adult BPHs, the expression pattern of NlChP38 was consistent with Fcp3C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the study on insect eggshells has occurred with lepidopterans (Kawasaki et al , 1971;Regier et al , 1978) and dipterans (Margaritis et al , 1980;Parks and Spradling, 1987;Fakhouri et al , 2006); the constituents and formation process of BPH eggshells remain largely unknown. A previous study revealed that N. lugens forkhead box transcription factor L2 (NlFoxL2 ) regulates follicle cell protein 3C (NlFcp3C ) (Ye et al , 2017) and a chorion protein (NlChP ) (Lou et al , 2018) during choriogenesis. Here, we report that NlChP38 , which is also downregulated after NlFoxL2 inhibition, is essential for eggshell formation in the BPH.…”
Section: Introductionmentioning
confidence: 99%
“…The qPCR reactions were performed as described by Ye et al. (). The qPCR was repeated three times for each gene.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of the late chorionic gene in silkworm is generally regulated by Bombyx Chorion Factors I (BCFI) and GATAβ. The Forkhead box transcription factor L2 (NlFoxL2) in Nilaparvata lugens directly activates follicle cell protein 3C ( NlFcp3C ) to regulate chorion formation [ 165 ].…”
Section: Biological Functionsmentioning
confidence: 99%